Vitamin A and D deficiencies associated with incident tuberculosis in HIV-infected patients initiating antiretroviral therapy in multinational case-cohort study - Tenforde, Mark W (J Acquir Immune Defic Syndr, 2017)
INTRODUCTION: Numerous micronutrients have immunomodulatory roles that may influence risk of tuberculosis (TB), but the association between baseline micronutrient deficiencies and incident TB after antiretroviral (ART) initiation in HIV-infected individuals is not well characterized. METHODS: We conducted a case-cohort study (n=332) within a randomized trial comparing three ART regimens in 1571 HIV treatment-naïve adults from nine countries. A subcohort of 30 patients was randomly selected from each country (n=270). Cases (n=77; main cohort=62, random subcohort=15) included patients diagnosed with TB by 96 weeks post-ART initiation. We determined pre-treatment concentrations of vitamin A, carotenoids, vitamin B6, vitamin B12, vitamin D, vitamin E, and selenium. We measured associations between pre-treatment micronutrient deficiencies and incident TB using Breslow-weighted Cox regression models. RESULTS: Median pre-treatment CD4+ T-cell count was 170 cells/mm(3); 47.3% were female; and 53.6% Black. In multivariable models after adjusting for age, sex, country, treatment arm, prior TB, baseline CD4 count, HIV viral load, body mass index, and C-reactive protein, pre-treatment deficiency in vitamin A (adjusted hazard ratio, aHR 5.33, 95% confidence interval, CI 1.54–18.43) and vitamin D (aHR 3.66, 95%CI 1.16–11.51) were associated with TB post-ART. CONCLUSION: In a diverse cohort of HIV-infected adults from predominantly low- and middle-income countries, deficiencies in vitamin A and vitamin D at ART initiation were independently associated with increased risk of incident TB in the ensuing 96 weeks. Vitamin A and D may be important modifiable risk factors for TB in high-risk HIV infected patients starting ART in resource-limited, highly-TB-endemic settings.